Tindak Tutur Mengkritik Netizen di Media Sosial X Terhadap Film Animasi Merah Putih One for All - Dilla, Frisca; Batubara, Nisa Anggraini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
Interactions carried out by netizens on social media can trigger various responses, both positive and negative. This study aims to analyze the speech acts of netizens criticizing the animated film Merah Putih One for All on social media X. The method used in this study is descriptive with a speech act theory approach that focuses on the speech act of criticizing. The data analyzed consisted of 100 critical utterances. Data collection was carried out using the free listening technique and note-taking technique. Data were collected by capturing images of comments and then transcribing them into written form. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions. The results of the study show that indirect criticism speech acts of condemnation are often found in netizen tweets on social media X. This indicates that the criticism expressed by netizens on social media is more negative than positive. It can be concluded that understanding netizen criticism on social media will provide insight for all policymakers and public figures to provide a good image and communication to the public.